A taxonomic study of the genus Austrohancockia Günther (Orthoptera:Tetrigoidea: Tetrigidae) - Deng, Weian; Zheng, Zhemin; Wei, Shizhen (Zootaxa, 2008)
Eleven species of Austrohancockia Günther were systematically researched in this paper. One species, Austrohancockia tuberfemora sp. nov., is described as new to science. This new species can be distinguished from Austrohancockia guangxiensis Zheng et Jiang, 1998, but differs in vertex and frontal ridge forming a right-angle; midkeel of pronotum interrupted, not conspicuous; pronotum reaching the knee of hind femur; width of fore femora equal to the width of middle femora; lower margins of fore and middle femora with one big teeth; third pulvillus of first segment of hind tarsi longer than first and second, apices of first and second sharp, apices of third obtuse. An updated key to the species of Austrohancockia is presented. The type specimens are deposited in the Institute of Zoology, Shaanxi Normal University, Xi’an, China.